Penerapan Prinsip Kehati-Hatian Sebagai Perlindungan Hukum Preventif dalam Pembuatan Akta Autentik Notaris - Zanuba Arifa Khafsof ZM; Amad Sudiro (UNES Law Review, 2023)
The purpose of writing this article is to be able to understand and analyze the application of the precautionary principle as preventive protection in making authentic notarial deeds. This article uses a normative research type with a statutory and regulatory research approach and a conceptual approach, and uses qualitative descriptive data analysis with deductive thinking methods. The form of the precautionary principle referred to above is a principle that is not regulated and strengthened in the UUJN, which causes notaries in carrying out their duties as public officials who make authentic deeds to often encounter legal problems, such as forgery of identity letters of the parties, certificates and false statements from the parties. . In this way, the notary will be vulnerable to being caught in a crime, namely falsifying documents due to negligence or committing a criminal act due to negligence. Based on Article 50 of the Criminal Code, it confirms that "whoever commits an act to carry out statutory regulations, must not be punished." Article 50 of the Criminal Code provides legal protection for the actions of Notaries as stated in Article 48 paragraph (1) of Law no. 2 of 2014, which regulates that the contents of the Deed are prohibited from being changed, which has the implication of binding the Notary in the criminal act of Negligence